Interdisciplinary approach allows minimally invasive, nerve-sparing removal of retroperitoneal peripheral nerve sheath tumors - Hajiabadi, Mohammad Mehdi; Campos, Benito; Sedlaczek, Oliver; Khajeh, Elias; Nikdad, Mohammadsadegh; Deimling, Andreas von; Mehrabi, Arianeb; Unterberg, Andreas; Ahmadi, Rezvan (Langenbeck's archives of surgery, 2020)
PURPOSE: En bloc resection of retroperitoneal peripheral nerve sheath tumors (PNST) is advocated by a variety of surgical disciplines. Yet, microsurgical, nerve-sparing tumor resection might be better suited to improve symptoms and maintain neurological function, especially in cases where patients present with preoperative neurological deficits. However, neurosurgeons, versed in nerve-sparing techniques to remove PNST, are generally unfamiliar with the visceral approaches to retroperitoneal PNST. METHODS: We retrospectively evaluate a series of 16 patients suffering from retroperitoneal PNST. Patients were treated by a unique interdisciplinary approach, combining the visceral surgeon's skills to navigate the complex anatomy of the retroperitoneal space and the neurosurgeon's familiarity with microsurgical, nerve-sparing tumor removal. Specifically, we assess whether our interdisciplinary approach is suited to improve preoperative symptoms and maintain neurological function and study whether oncological outcome, surgical morbidity, and operative times are comparable to those reported for "classical" retroperitoneal PNST resection. In addition, we study two cases of suspected PNST that were diagnosed as malignant peripheral nerve sheath tumors (MPNST) after surgery. RESULTS: Total macroscopic tumor resection was achieved in 14/16 PNST patients. Mean intraoperative blood loss was 680.6 ml (95% CI, 194.3-1167.0 ml) and mean operative time was 162.5 min (95% CI, 121.6-203.4 min). We did not record any major postoperative surgical or neurological complications. A total of 8/11 patients with preoperative pain symptoms reported long-lasting improvement of their symptoms. In terms of oncological outcome, all patients that had been subjected to total tumor removal and for whom follow-up was available, were tumor-free after a mean follow-up of 761.9 days (95% CI, 97.6-1426.0 days). One of the two MPNST patients, who presented with tumor progress 15 months after initial surgery, was subjected to radical re-resection. CONCLUSIONS: Interdisciplinary, nerve-sparing removal of retroperitoneal PNST is well suited to improve preoperative symptoms and maintain neurological function, while achieving an oncological outcome and a surgical morbidity similar to previously reported results for radical retroperitoneal PNST resection. Radical re-resection was feasible in a patient with post hoc MPNST diagnosis.
Gesehen am 24.06.2020